Stochastic heating of electrons in capacitive RF discharges by plasma oscillations - Manuilenko, O.V. (Вопросы атомной науки и техники, 2012)
Stochastic heating of electrons by plasma oscillations excited in the capacitive discharge plasma is investigated theoretically. We have obtained criteria, when the stochastic heating take place, and demonstrated numerically that this heating mechanism can be sufficiently effective.